Retrospective study on susceptibility and resistance pattern of urinary pathogens in a tertiary care hospital - Ramu, Sudha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Indiscriminate and inappropriate use of antimicrobial agents (AMA) resulted in rapid emergence of antimicrobial resistance. Institutional level surveillance program to be carried out to track AMA use. The study was conducted to evaluate the prevalence of uropathogens and their susceptibility and resistance pattern in a tertiary care hospital to revise empirical therapy. Methods: Urine samples received from the inpatients and outpatients Departments of Mahatma Gandhi memorial hospital for culture sensitivity between January 2018 to December 2018 were included in this study. Data collected from the Department of Microbiology register by using WHONET software. After identification, isolates were tested for antimicrobial susceptibility by the standard Kirby Bauers diffusion method. Descriptive analysis done and results were expressed as percentage. Results: Out of 3425 samples 68.5% showed no growth, 15.5% normal flora and only 15.9% reported as culture positive. In this study the highest isolate was Escherichia coli (59%) followed by Klebsiella pneumoniae (10.6%), Enterococcus sp. (7%), Staphylococcus aureus (5%), Candid (3.6%), Acinetobactor (3%) and Pseudomonas (2.9%). Uropathogens developed resistance against penicillins, cephalosporins, macrolides and cotrimaxazole. Conclusions: This study confirms, the frequently prescribed empirical therapy drugs were less susceptible and developed resistance than less frequently prescribed and costly drugs. The current antimicrobial resistance pattern alarms the irrational and excessive use of antimicrobial agents. Hence the treating physicians should revise empirical therapy periodically based on the institutional antibiogram and resistance pattern reported from the laboratory to preserve antimicrobial source for the future generation.